Thermodynamics and microstructure of vacancies in rare gas crystals at high temperature - Karasevskii, A.I.; Lubashenko, V.V. (Физика низких температур, 2007)
A self-consistent statistical method is used to calculate the Gibbs free energy of vacancy formation in
heavy rare gas crystals at high temperature. It is shown that the vacancy formation free energy rapidly falls
in the vicinity of the melting point of the crystal. Such behavior is attributed to approaching the anharmonic
instability point of vibrational subsystem of the solid.